Additive manufacturing technologies with emphasis on stereolithography 3D printing in pharmaceutical and medical applications: A review - Lakkala, Preethi; Munnangi, Siva Ram; Bandari, Suresh; Repka, Michael (International journal of pharmaceutics: X, 2023)
Three-dimensional (3D) printing or Additive Manufacturing (AM) technology is an innovative tool with great potential and diverse applications in various fields. As 3D printing has been burgeoning in recent times, a tremendous transformation can be envisaged in medical care, especially the manufacturing procedures leading to personalized medicine. Stereolithography (SLA), a vat-photopolymerization technique, that uses a laser beam, is known for its ability to fabricate complex 3D structures ranging from micron-size needles to life-size organs, because of its high resolution, precision, accuracy, and speed. This review presents a glimpse of varied 3D printing techniques, mainly expounding SLA in terms of the materials used, the orientation of printing, and the working mechanisms. The previous works that focused on developing pharmaceutical dosage forms, drug-eluting devices, and tissue scaffolds are presented in this paper, followed by the challenges associated with SLA from an industrial and regulatory perspective. Due to its excellent advantages, this technology could transform the conventional “one dose fits all” concept to bring digitalized patient-centric medication into reality. [Display omitted]